Corrosion resistant behaviour of titanium – Molybdenum alloy in sulphuric acid environment. (2022) - Shree Meenakshi, K.; Ananda Kumar, S.
Abstract: The present work focuses on the corrosion prevention behaviour of pure titanium metal (Ti) and its alloy with various percentages of molybdenum (Mo) in sulphuric acid environment. The alloying of pure Ti was made using 5, 10, 15% of Mo and their corrosion resistance in acidic environment was evaluated by electrochemical techniques namely potentiodynamic polarization and electrochemical impedance spectroscopy (EIS). The effectiveness of the alloy in improving the corrosion resistance was monitored by means of Nyquist and Bode plots resulted from impedance studies. Potentiodynamic polarization studies were also carried out for the pure Ti metal and its alloy with different concentration of Mo in acid environment. The data resulted from the above two electrochemical studies reveal that Ti 85- Mo 15 was found to offer the maximum corrosion resistance than pure Ti and its other alloys with Mo. It was also interesting to note that with increase in molybdenum content the corrosion resistance of the Ti alloy kept on increasing.